Nutritional Elements and Heavy Metals in Tibetan Medicine Terminalia chebula - Sun, Peng; Rui, Yu-Kui; Li, Xianen (Asian Journal of Chemistry, 2011)
Wild Terminalia chebula from Tibet were determined the contents of nutritional elements and heavy metals by ICP-MS to evaluate its quality. The results showed that there are many kinds of nutritional elements in wild Terminalia chebula from Tibet of China, i.e., Ca, Fe, Mn, Zn, Cu, Se and Mo, whose contents were 756.33 μg/g, 133.98 μg/g, 6.75 μg/g, 9.48 μg/g, 4.81 μg/g, 316.27 ng/g and 10.98 ng/g respectively. The contents of four kinds of heavy metals i.e., As 160.81 ng/g, Cd 14.86 ng/g, Pb 71.65 ng/g and Cr 184.40 ng/g, respectively in Terminalia chebula from Tibet. Compared with Tibetan medicine Potentill ta anscri na L. from Gansu proveince, Terminalia chebula from Tibet contained more As and less Cd and Pb. It is concluded that Terminalia chebula from Tibet meet to the standard "Green Professional Standard for Importing and Exporting Medicinal Herbs and Preparations" in terms of nutritional elements and heavy metals.